Meningkatkan Minat Baca dan Literasi Mahasiswa melalui Kegiatan Bedah Buku Atomic Habits - Minarti Usman; Erma Pratiwi Nufi; Fitrianingsih Fitrianingsih (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
The declining reading interest among university students, particularly toward printed books, has become an issue that requires serious attention in the digital era characterized by various distractions. Low student engagement in reading activities negatively affects literacy skills, conceptual understanding, and the development of critical thinking. This community service activity aimed to enhance students’ reading interest, reading comprehension literacy, as well as critical thinking and communication skills through a book review activity of Atomic Habits by James Clear. The activity was conducted on December 19, 2025, involving 25 participants consisting of students from the Guidance and Counseling Study Program and volunteers from Dompet Dhuafa. The implementation method employed a dialogical approach and interactive discussions, beginning with a material presentation by the facilitator, followed by question-and-answer sessions and reflective discussions. The results indicated an increase in participants’ reading interest, as measured by high attendance rates and active participation during discussions. More than 80% of participants were actively involved in asking questions and expressing opinions. In addition, participants demonstrated improved understanding of the book’s content, enhanced ability to present logical arguments, and increased confidence in communicating in a forum. This activity also resulted in the formation of an active reading community as a follow-up effort to strengthen literacy culture. Therefore, the book review activity proved to be an effective community service strategy for sustainably improving students’ reading interest and literacy competencies